Dari Limbah Menjadi Berkah: Edukasi Kreatif melalui Mozaik Kulit Telur untuk Pemberdayaan Masyarakat - Donant Alananto Iskandar; Ignatius Ario Sumbogo; Anjar Dwi Astono; Siti Ruhana Dara; Vina Meliana; Maulana Malik Muhammad; Triyono Arief Wahyudi (LPMP Imperium, 2026)
The utilization of eggshell waste offers a sustainable solution to reducing the environmental impact of organic waste while providing economic value to local communities. This program aims to develop educational strategies and community empowerment through practical training on processing eggshell waste into value-added products. Implemented using a participatory approach, the activity actively engaged community members in both learning and hands-on practice. The training focused on transforming eggshells into organic fertilizer, handicrafts, and animal feed additives. The event was conducted on October 2, 2025, in Pancoran, South Jakarta, in collaboration with the Family Welfare Movement (PKK) RW 3 as the primary community partner. PKK’s strategic role in fostering community welfare and facilitating information dissemination made them an ideal collaborator for this initiative. The success of the program is reflected in increased community knowledge and skills, strong participant engagement, the emergence of recycling-based entrepreneurial ideas, and strengthened partnerships between the implementation team, PKK RW 3 Pancoran, and the local community.